Using Western Social Theory: Towards a Moral Ethnography of Islamic Boarding Schools in West Sumatra, Indonesia - Lynette Parker (Asia-Pacific Journal on Religion and Society, 2021)
This paper aims to map various Western social theories so that they can be used in writing "moral ethnography" in modern Islamic boarding schools in the Minangkabau, West Sumatra, Indonesia. In this paper, the author shows how the three theoretical approaches allow different ethnographic production, in the search for ethnographic theoretical approaches that are appropriate to the moral goals of the form of education. The author begins with Goffman's "total institution" idea, which Goffman used as the basis of his book on "asylum" or mental hospital. It seems that the concept of "total institution" is very suitable for the description of the pesantren, and indeed Goffman followed the school with a guesthouse as an example of a total institution. The author shows how to use the example of a total institution to give life to the results of the particular description of pesantren. In this picture, it seems that the substitute Islamic boarding school is rather harsh, with a strong institutional structure, strong boundary patrols (and separation from family and society), and a very tight and regular day-to-day schedule. Then, the author explains Foucault's theory of power, tight relations or nexus between power and knowledge, and discourse, and elaborates how to apply this idea to ethnographic data. The author shows that these concepts are very powerful tools for the ethnography of Islamic boarding schools. In particular, the image of "panopticon" as a review tool from above, and the idea of "bio-power" (bio power) and "pastoral power" are suitable for showing the aspects or nature of the pesantren's sub-culture. Islamic boarding schools create santri who are very reviewing themselves and their friends, who really want to be open to the observation of Allah and to pesantren leaders, and are interested in living morally, and improving themselves, through knowledge and faith.This paper aims to map various Western social theories so that they can be used in writing "moral ethnography" in modern Islamic boarding schools in the Minangkabau, West Sumatra, Indonesia. In this paper, the author shows how the three theoretical approaches allow different ethnographic production, in the search for ethnographic theoretical approaches that are appropriate to the moral goals of the form of education. The author begins with Goffman's "total institution" idea, which Goffman used as the basis of his book on "asylum" or mental hospital. It seems that the concept of "total institution" is very suitable for the description of the pesantren, and indeed Goffman followed the school with a guesthouse as an example of a total institution. The author shows how to use the example of a total institution to give life to the results of the particular description of pesantren. In this picture, it seems that the substitute Islamic boarding school is rather harsh, with a strong institutional structure, strong boundary patrols (and separation from family and society), and a very tight and regular day-to-day schedule. Then, the author explains Foucault's theory of power, tight relations or nexus between power and knowledge, and discourse, and elaborates how to apply this idea to ethnographic data. The author shows that these concepts are very powerful tools for the ethnography of Islamic boarding schools. In particular, the image of "panopticon" as a review tool from above, and the idea of "bio-power" (bio power) and "pastoral power" are suitable for showing the aspects or nature of the pesantren's sub-culture. Islamic boarding schools create santri who are very reviewing themselves and their friends, who really want to be open to the observation of Allah and to pesantren leaders, and are interested in living morally, and improving themselves, through knowledge and faith.